A case of giant prolactinoma and pituitary hemorrhage with the late recovery of pituitary function: A case report - Lakshmi P Menon; Dinesh Edem (SAGE Open Medical Case Reports, 2023)
Hypogonadotropic hypogonadism is a common finding in patients who are diagnosed with a prolactinoma. It can be accompanied by the presence of other pituitary hormone deficits, including secondary adrenal insufficiency and central hypothyroidism. While the proportion of improvement in endocrine deficits over the short term is well characterized, there is not enough literature about the recovery of pituitary function over the longer term. We present the case of a 23-year-old man with a giant prolactinoma who initially presented with pituitary hemorrhage and panhypopituitarism. He underwent decompression of the pituitary tumor followed by treatment with cabergoline. Over a 9-year follow-up period, we noted that the hypogonadotropic hypogonadism resolved after 4 years and the secondary adrenal insufficiency resolved after 8 years. This case suggests that partial or complete recovery of the pituitary function is possible over the long-term even in patients with a giant prolactinoma.